The Influence of Compensation and Training toward Work Discipline and Its Impact on the Employees’ Performance in the Research Center of Science and Technology (PUSPIPTEK) - Andhi Bharata (Bina Nusantara University, 2016)
Background issues that occured in PUSPIPTEK (Research Center of Science and Technology) was the declining of employee performance, low discipline in work such as not obeying the rules, and decreased absenteeism as coming late to the office. The purpose of this study was to determine the effect of compensation on, the effect of training on work discipline, the effect of compensation on employee performance, the effect of training on employee performance, the effect of work discipline on employee performance, and the effect of compensation and training to the work discipline and its impact on employee performance PUSPIPTEK. This research was associative and the measurement scale applied likert scale. The method of analysis used was path analysis and the number of samples in this study was 116 respondents. Based on the result, this study concludes that the compensation and training toward the work discipline has a significant influence on the employees’ performance. The empirical findings indicate that in order to improve the employees’ performance in PUSPIPTEK need to pay attention on compensation, training, and work discipline.